(untitled) (Journal of the College of Basic Education, 2026)
The coupling of opposing dualities in commercial advertisement designs is a justified approach. The inclination of each duality toward the other confirms their convergence, culminating in a merger into a unified completely where each serves as a cornerstone for the other. In his creative process, the designer departs from a preconceived idea; he is the very originator of ideas and concepts. Thus, the forms he employs within the design process are perpetually renewed in meaning. The first chapter addressed the following question: What are the opposing dualities and their reflections in commercial advertisement designs? The aim of the research is to identify the opposing dualities and their reflections in commercial advertisement designs. The significance of the research lies in: Its contribution to offering a novel perspective for analyzing visual discourse through the lens of opposing dualities. Enriching Iraqi and Arab libraries, as well as the resources available to specialists—both in specific and general fields—on the topic of opposing dualities. The second chapter included the first section (The Concept of Opposing Dualities), while the second section was (The Duality of Presence and Absence and its Reflections in Commercial Advertisement Designs). The third chapter presented the conclusions, which were as follows: The dualities were manifested through a synthesis of elements that achieved a formal dimension, alternating between the formal presence and partial absence of other elements. The mechanism of presence oscillated between the apparent description of a form, whose meaning-completing details were absent, thus allowing for the presence of another form laden with added meaning to the design unit, which was centralized within the design field of the commercial advertisements. The dualities embodied a clear contrast in the design proposal by establishing a discourse operating on both the formal and semantic levels, conveying opposing significations that achieve a meaning fundamental to commercial advertisements. As for the recommendations, the two researchers recommended the following: Urging designers to investigate and explore the best methods to keep pace with scientific advancement through experimentation and the use of state-of-the-art software, in order to advance towards a new and effective design future in the application of opposing dualities. The study recommends integrating the duality of Presence and Absenceinto design curricula within postgraduate programs across various disciplines.